(untitled) (Bangladesh Journal of Botany, 2026)
This study assessed the arsenic tolerance of seven rice cultivars (BRRI Dhan 92, 99, 100, 101, 102, 104, and 105) based on germination performance and early seedling growth. Seeds were exposed to 0, 5, 10, 15, and 20 ppm arsenic for 14 days. Arsenic markedly diminished germination percentage, index and speed of seed emergence, as well as the seedling growth parameters including root and shoot length, and their fresh and dry weight. Among the cultivars, BRRI Dhan 105 showed the highest tolerance across all treatments, with 81.67% germination percentage and 76.42% germination speed at 20 ppm arsenic, while BRRI Dhan 104 recorded the lowest performance with 10.00% GP and 8.48% GS. Growth metrics consistently declined with increasing arsenic concentration. BRRI Dhan 105 showed a relative resilience for the majority of the parameters, resulting into a reduction rate of 48.21 and 69.97% in the length and fresh weight of the shoot. Whereas, the declining rate was highest in BRRI Dhan 104 (70.28 and 74.61%) and comparatively higher in BRRI Dhan 99 (58.37 and 80.92%). Overall, BRRI Dhan 105 was identified as the comparatively more arsenic-tolerant cultivar during germination and seedling stages, while BRRI Dhan 99 and 104 were highly susceptible.